Digital Platform as a Arabic Morphology Science Learning Solution for Generation Z - Hidayat, Rahmat; Syuhadak, Syuhadak; Agil, Idrus Muchsin Bin (UIN Mahmud Yunus Batusangkar, Indonesia, 2024)
Learning Sharfi science is a fundamental element in mastering Arabic, but conventional methods are often considered monotonous and ineffective, especially for Generation Z who are familiar with technology. This study aims to evaluate the effectiveness of digital platforms in learning Sharfi science. With a quantitative survey approach, 22 students of Mahmud Yunus Batusangkar State Islamic University were involved as respondents. Data was collected through a digital-based questionnaire designed to measure students’ perception of the effectiveness of using digital platforms in learning. The results of the study showed that 90% of respondents felt easy in understanding Sharfi’s material through digital media. In addition, 57% of them routinely use digital platforms in the learning process. These findings confirm that digitization of learning can increase student engagement as well as the effectiveness of the learning process. Popular platforms like Canva and YouTube have proven to be able to present learning concepts in a more interactive and engaging way. This study concludes that the use of digital technology not only makes learning more dynamic, but also relevant to the needs of the current generation. This finding has important implications for the further development of digital teaching materials to support Sharfi learning that is more effective and engaging. This study recommends increasing innovation in the provision of technology-based learning materials to optimize the potential of digitalization in the field of Arabic language education.